Voxel-Wise Analysis of Diffusion Tensor Imaging for Clinical Outcome of Cochlear Implantation: Retrospective Study - Chang, Yongmin; Lee, Hye-Ryung; Paik, Jong-Soo; Lee, Kyu-Yup; Lee, Sang-Heun (Clinical and experimental otorhinolaryngology, 2012)
To evaluate retrospectively, the possible difference in diffusion tensor imaging (DTI) metric of fractional anisotropy (FA) between good and poor surgical outcome cochlear implantation (CI) patients using investigator-independent voxel-wise analysis. Eighteen patients (11 males, 7 females; mean age, 5.9 years) with profound sensorineural hearing loss underwent DTI scans using a 3.0 Tesla magnetic resonance scanner. Among the 18 patients, 10 patients with categories of auditory performance (CAP) score over 6 were classified into the good outcome group and 8 patients with CAP score below 6 were classified into the poor outcome group. The diffusion tensor scalar measure was calculated from the eigenvalues of the tensor on a voxel-by-voxel basis from each subject and two-sample t-test evaluation between good and poor outcome subjects were performed for each voxel of FA values, across the entire brain, with a voxel-wise intensity threshold of P<0.0005 (uncorrected) and a contiguous cluster size of 64 voxels. Individual values of FA were measured by using the region-of-interest based analysis for correlation analysis with CAP scores, open sentence and open word scores. Two-sample t-test evaluation using SPM voxel-wise analysis found significantly higher FA values at the several brain areas including Broca's area, genu of the corpus callosum, and auditory tract in good outcome subjects compared to poor outcome subjects. Correlation analyses between FA and CAP scores, open sentence and open word scores revealed strong correlations at medial geniculate nucleus, Broca's area, genu of the corpus callosum and auditory tract. Investigator-independent voxel-based analysis of DTI image demonstrated that good outcome subjects showed better neural integrity at brain areas associated with language and auditory functions, suggesting that the conservation of microstructural integrity of these brain areas is important. Preoperative functional imaging may be helpful for CI.